El berrinche de Aquiles. - Bolaños López, Zahyra (2012)
This paper analyzes the Homeric concept of Achille's hybris and the existing relationship between self and fate, whose dire consequences and further reflection on the value of human life could be considered as a strong and undeniable cry for peace. For this reason, it constitutes the legacy to posterity by the Poet of the Iliad.